The Effect of Think Pair Share Cooperative Learning Model on Students' Conceptual Understanding Ability - Perangin-angin, Fanny Selfinta; Lubis, Nur Ainun (Media Pendidikan Matematika, 2025)
This study aims to investigate the effect of the Think Pair Share (TPS) type of cooperative learning model on students’ conceptual understanding of mathematics, specifically on the topic of Three-Variable Linear Equation Systems. The research was conducted at SMAS Budisatrya Medan using a quantitative approach with an experimental method and a quasi-experimental pretest-posttest control group design. The sample consisted of 64 tenth-grade students divided into two groups: an experimental class that received instruction using the Think Pair Share model, and a control class that was taught through conventional methods. The pretest results indicated that the average initial score of students in the experimental class was 6.62, while the control class averaged 5.50. After the intervention, the posttest scores increased to 17.75 in the experimental class and 14.00 in the control class. The difference in score improvement was statistically significant, as evidenced by a t-test result of t = 6.387 with a significance level of p = 0.000. These findings suggest that the Think Pair Share model significantly enhances students’ conceptual understanding of mathematics compared to traditional teaching methods. The researchers recommend the use of this model as an effective alternative for mathematics instruction, as it not only improves learning outcomes but also fosters social interaction, critical thinking, and students’ self-confidence. Keywords: cooperative learning, think pair share, conceptual understanding, mathematics